Gleaming Coffins - Rogério Sousa (Outros Títulos, 2018)
Egyptian coffin decoration is a complex and multidimensional phenomenon with its own history and evolution. 'Yellow' coffins were crafted in Thebes during a particular critical period in the Egyptian History, witnessing to a situation of political unrest and severe economic scarcity affecting Egypt, the Near East and the Mediterranean. And yet, there is no evidence for a decline in the production of these outstanding funerary artefacts. On the contrary, the corpus of 'yellow' coffins outnumbers the previous types of Egyptian anthropoid containers and stands out among the most complex and sophisticated objects ever crafted in the Ancient World. Besides this historical paradox, the 'yellow' corpus presents important epistemological challenges for our understanding of Egyptian material culture: what kind of space is created within the walls and forms of an anthropoid coffin? What role plays variability and change in this process? Last but not the least, can we understand the meaning behind the multiple shapes and endless variations adopted in coffin decoration during this period? This book addresses these questions presenting the results of a comparative study on coffin decoration involving an extensive sample of objects from the 'yellow' corpus dispersed in museums around the world. The results of this study reveal the principles of composition that ruled the work of the ancient Theban craftsmen and show how important coffin decoration was for the Theban priesthood of Amun to convey their own corporative values.